Effect of Spraying with Algae Extract, Arginine and Brassinolide on Chemical Content of Strawberry Saplings cv. Albion - Al-Dulaimy, Ahmed; Al-Ealayawi, Zeyad (PROSPECTIVE RESEARCHES, 2024)
The study was conducted in Al-Anbar province at two sites, the first one was in the research station belonging to the College of Agriculture- University of Anbar, and the other one was in Al-dolab Village during the growth season of 2022 – 2023. The aim of the study was to the effect of spraying the strawberry plants (var. Albion) with Seaweed extract, Arginine, and Brassinosteroid under a controlled environment. Seaweed extract was applied in three levels which were 0, 2 and 4 ml L-1), while the Arginine was sprayed with 0, 100 and 200 mg L-1 and the Brassinosteroid concentrations were 0, 0.05 and 0.10 mg L-1. The factorial experiment carried out by RCBD design includes 27 experimental units repeated three times. Each experimental unit included five plants and the obtained data was analyzed by using the (L.S.D.) at the level of probability of 0.05. Spraying with Seaweed extract showed a significant effect on all the studied traits, and the concentration (4 ml L-1) achieved the best results for the traits; leaves chlorophyll, carbohydrates and NPK nutrients content were (11.78 and 11.13 mg gm-1, 13.82 and 12.83%, 2.50 2.40%, 0.184 and 0.176%, 1.64 and 1.60%) for first and second location, respectively. As for spraying the strawberry plants with the amino acid (arginine) was significant for all the traits studied, and the concentration (200 mg L-1) has achieved the best results for the traits (leaves content of carbohydrates and NPK nutrients) for the first and second sites amounted to (13.91 and 12.53%, 2.48 and 2.37%,0.183 and 0.176%, 1.59 and 1.61%), respectively. As for the chlorophyll content of the leaves, it appeared at its highest levels at the concentration of (100 mg L-1) reaching (11.68 and 10.69 mg g-1) at both sites, respectively. On the other hand the obtained results showed that spraying treatments with the growth regulator (Brassinosteroid) had a significant effect on all the studied traits except the leaves content of carbohydrates for both sites, and the concentration (0.10 mg L-1) contributed to achieving the best results for traits; leaves content of chlorophyll and elements NPK which were 11.87 and 10.71 mg gm-1, 2.48 and 2.37%, 0.180 and 0.172%, 1.56 and 1.56% at both study sites, respectively. Furthermore, the above concentration achieved the highest values for the leaves content of carbohydrate at the first site which was 13.88%. Otherwise the two and three-way interactions between the study factors reached the significance level depending on the type of trait studied